Spectral principal component analysis of mid-infrared spectra of a sample of PG QSOs. Issue 4 (13th January 2016) - Bian, Wei-Hao; He, Zhi-Cheng; Green, Richard; Shi, Yong; Ge, Xue; Liu, Wen-Shuai
Abstract: A spectral principal component (SPC) analysis of a sample of 87 Palomar-Green (PG) QSOs at z < 0.5 is presented for their mid-infrared spectra from Spitzer Space Telescope. We have derived the first five eigenspectra, which account for 85.2 per cent of the mid-infrared spectral variation. It is found that the first eigenspectrum represents the mid-infrared slope, forbidden emission line strength and 9.7 μm silicate feature; the 3rd and 4th eigenspectra represent the silicate features at 18 and 9.7 μm, respectively. With the principal components (PC) from optical principal component analysis, we find that there is a medium strong correlation between spectral SPC1 and PC2 (accretion rate). It suggests that more nuclear contribution to the near-IR spectrum leads to the change of mid-IR slope. We find mid-IR forbidden lines are suppressed with higher accretion rate. A medium strong correlation between SPC3 and PC1 (Eddington ratio) suggests a connection between the silicate feature at 18 μm and the Eddington ratio. For the ratio of the silicate strength at 9.7 μm to that at 18 μm, we find a strong correlation with PC2 (accretion rate or QSO luminosity). We also find that there is a medium strong correlation between the star formation rate (SFR) and PC2. It implies a correlation between SFR and the central accretion rate in PG QSOs.